Military Dictatorship, University Reform, and Teacher Education in Chile: The Historical Emergence of a Dysfunctional Structure - Cox, Cristián; Sánchez Bachman, Macarena (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2023)
The article describes the evolution of public policies related to teacher education inChile during the period of the military dictatorship (1973-1990) and the paradoxicalimpact of university reform in teacher education at the end of the 1960s. Bothprocesses are connected to examine the roots of the inability of teacher education tomeet the necessary requirements following the structural changes produced by the1960 reform. The reform extended primary education by two grades, therebybroadening and complexifying both the curriculum and the student population. Giventhat the initial implementation of the reform coincided with the political crisis thatculminated in the coup d'état, it can be understood why neither teacher educationpolicies nor teacher preparation institutions responded to this change. Unfortunately,during the quarter of a century that followed, there was a persistent failure to adaptto the changes that the 1960 reform had wrought. Thus, a dysfunctional structure ofteacher education remained, one that did not respond to the structure of the schoolsystem it sought to serve. In terms of its analytical and interpretative purpose, thepaper combines historical policy analysis, sociological interpretation of the dynamics of higher education, and an extended analysis of how disciplinary and pedagogicalknowledge came to be disconnected in teacher education.